MISI POLITIK SASTRAWAN LEKRA DALAM PERJUANGAN KELAS PEKERJA DI INDONESIA: HISTORIOGRAFI SASTRA INDONESIA PERIODE 1960-AN - Fikri, Moh. Fikri Zulfikar; Saryono, Djoko; Syahri, Moch.; Maulana, M. Abidzar; Huda, Much. Nuril (University of Brawijaya, 2024)
As a cultural institution that houses various arts and literature activities, the People's Cultural Institute (Lekra) has a strong political mission and ideals. Lekra fought to restore love for native culture and culture originating from the people who have high moral values. The people in question are farmers and laborers who are the source of the birth of Indonesian culture. From there, Lekra fought so that the culture carried by the people, especially farmers and laborers, could remain strong and not just as entertainment, but for the welfare of the working class. For Lekra, all efforts in art and literature are only for the people because art and literature are truly for the people. The purpose of this study is to write the historical discourse of Lekra literary works in carrying out political missions in the struggle of the working class in Indonesia. This study uses a qualitative research type with a historiographic approach. The research data refers to a group of information from reading texts. The data sources for this study are various information in the form of newspaper texts, books, articles, and videos that explain the historical discourse of Lekra's political literary mission. The data collection technique for this study was carried out using reading, note-taking, and document study techniques. The results of this research are that there are three things in the political mission of Lekra writers in the working class struggle in Indonesia: (1) unilateral action by farmers and workers as a source of inspiration, (2) the partisanship of Lekra writers in the working class resistance, and (3) the political mission of raising awareness for farmers and workers.